Revisiting energy efficiency, renewability, and sustainability indicators in biofuels life cycle: Analysis and standardization proposal. (10th April 2020) - Mayer, Flávio Dias; Brondani, Michel; Vasquez Carrillo, Maria Cecilia; Hoffmann, Ronaldo; Silva Lora, Electo Eduardo
Abstract: Life Cycle Energy Analysis (LCEA) has been widely used for net energy balance and energy ratio calculation, expressing the overall efficiency, renewability, and sustainability of biofuels production. However, over 27 methodologies have been found in the literature, representing a barrier for the comparison between different studies. The aim of this research is to discuss the main LCEA indicators methodologies and to propose a more comprehensive and user-friendly system of standard equations for the calculation of energy efficiency indicators, considering allocation criteria and renewability of energetic inputs. The standardized equations were evaluated via their application in two case studies related to sugarcane ethanol and biodiesel production and the results were compared to evaluate the influence of allocation criteria and inputs characteristics (renewable and non-renewable) in both attributional and consequential LCEA. As a result, 10 methodologies were proposed in order to standardize those 27 energy indicators. It was observed a significant variation in energy values depending on the use of allocation criteria, which were 114–468% for attributional LCEA and 114–387% for consequential LCEA in ethanol production, and between a range of 106–147% for attributional LCEA and 159–212% for consequential LCEA, in biodiesel production. The consideration of renewable energy inputs resulted in energy variations between 99 and 428% (attributional LCEA) and 61–268% (consequential LCEA) in ethanol production and between 47 and 76% (attributional LCEA) and 78–114% (consequential LCEA) in biodiesel production. Also, results showed that allocation criteria, input characteristics, and LCEA approach have a significant influence on the energy balance. Standardized methodologies proposed for energy balance equations in a biofuel production system make easier the application, understanding, and comparison among results of an LCEA. Highlights: Twenty-seven methodologies on Life Cycle Energy Analysis were found. Multiplicity of methodologies results in difficulties to compare studies on biofuels. A new set of comprehensive energy indicators was proposed avoiding ambiguities. Energy indicators may vary in up to 400% depending on considerations.